2022
DOI: 10.14710/anuva.6.2.217-230
|View full text |Cite
|
Sign up to set email alerts
|

Pemetaan Pengetahuan Lokal Sunda di Kampung Naga-Tasikmalaya

Abstract: Masyarakat yang menempati Kampung Naga-Tasikmalaya adalah contoh masyarakat yang masih menjaga adat istiadat Sunda. Mereka hidup dengan menerapkan pengetahuan lokal yang mereka warisi dari leluhur. Penelitian ini bertujuan untuk memetakan jenis-jenis pengetahuan lokal yang mereka miliki. Oleh sebab itu kami menggunakan penelitian kualitatif dengan pendekatan analisis tematik untuk mendapatkan tema dari masing-masing pengetahuan lokal. Hasil penelitian ini menunjukkan bahwa masyarakat di Kampung Naga memiliki p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
2
1
0
2
Order By: Relevance
“…Local knowledge is characteristic of the culture of a local community. This is in accordance with the explanation from Mazlan and Omar that local knowledge is the ability of the community to contain beliefs and teachings that apply to certain groups [1]. This knowledge comes from parents, traditional leaders or elders from local groups in the traditional village area.…”
Section: The Concept Of Conservation Of Local Knowledge and Indigenou...supporting
confidence: 86%
See 1 more Smart Citation
“…Local knowledge is characteristic of the culture of a local community. This is in accordance with the explanation from Mazlan and Omar that local knowledge is the ability of the community to contain beliefs and teachings that apply to certain groups [1]. This knowledge comes from parents, traditional leaders or elders from local groups in the traditional village area.…”
Section: The Concept Of Conservation Of Local Knowledge and Indigenou...supporting
confidence: 86%
“…Local knowledge is a habit passed down through oral tradition from one generation to the next or a reflection of the life of the local community. This is in accordance with the explanation from Mazlan and Omar [1]. That local knowledge is the ability of the community to contain beliefs and teachings that apply to certain groups.…”
Section: Introductionsupporting
confidence: 89%
“…In line with that, Ani et al [35] reported that knowledge about traditional medicinal plants was limited and only passed down from generation to generation. Furthermore, Nurislaminingsih et al [36] reported that limited ancestral memory is one of the obstacles to preserving medicinal plant knowledge.…”
Section: Socio-economic Status Of the Sidodadi Village Communitymentioning
confidence: 99%
“…Hasil penelitian ini menunjukkan bahwa masyarakat Kampung Naga memiliki keunikan pengetahuan yang masih dipertahankan hingga saat ini (Nurislaminingsih et al, 2022). Tujuan dari penelitian ini adalah untuk mengetahui jenis-jenis kearifan lokal masyarakat Kampung Naga yang dipertahankan pada masa modern saat ini.…”
Section: Penggunaan Lahanunclassified